Rola Ducha Świętego w życiu Kościoła na podstawie "Komentarza do Dziejów Apostolskich" Bedy Czcigodnego († 735). - Wygralak, Paweł (Vox Patrum, 2024)
The article presented here discusses the teaching of Bede the Venerable in his commentary on the Acts of the Apostles on the role of the Holy Spirit in the life of the Church. The author of the commentary dedicates little space to discussing the truth of the divinity of the Holy Spirit. Much more extensively, in keeping with the content of the Acts, he elaborates on His role in the life of the first-century Church. Thus, He equips the Apostles with the necessary gifts to preach the Gospel. He supports them with wisdom when they make important decisions for the Church, is present in the sacrament of baptism, overcomes evil spirits and prompts the faithful to renew their lives. All who wish to receive the gifts of the Holy Spirit must abandon sin and open themselves to His works through prayer. Bede's teaching on the Holy Spirit is embedded in the tradition of the Fathers of the Church and has a decidedly pastoral dimension.